2015
DOI: 10.1093/toxsci/kfv230
|View full text |Cite
|
Sign up to set email alerts
|

Skin Damage Mechanisms Related to Airborne Particulate Matter Exposure

Abstract: Epidemiological studies suggest a correlation between increased airborne particulate matter (PM) and adverse health effects. The mechanisms of PM-health effects are believed to involve oxidative stress and inflammation. To evaluate the ability of PM promoting skin tissue damage, one of the main organs exposed to outdoor pollutants, we analyzed the effect of concentrated ambient particles (CAPs) in a reconstructed human epidermis (RHE) model. RHE tissues were exposed to 25 or 100 µg/ml CAPs for 24 or 48 h. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 42 publications
4
129
0
1
Order By: Relevance
“…O 3 has been shown to increase cytochrome p450 activation via the AhR 27. Recently, a direct action has been suggested by penetration through the stratum corneum 28. Once in the skin, the ROS cause a lipid peroxidation cascade, which stimulates the release of other proinflammatory mediators from keratinocytes and melanocytes, thus establishing a vicious inflammatory cycle, with infiltration of other potentiating cells such as neutrophils and other phagocytic cells 5.…”
Section: Resultsmentioning
confidence: 99%
“…O 3 has been shown to increase cytochrome p450 activation via the AhR 27. Recently, a direct action has been suggested by penetration through the stratum corneum 28. Once in the skin, the ROS cause a lipid peroxidation cascade, which stimulates the release of other proinflammatory mediators from keratinocytes and melanocytes, thus establishing a vicious inflammatory cycle, with infiltration of other potentiating cells such as neutrophils and other phagocytic cells 5.…”
Section: Resultsmentioning
confidence: 99%
“…There is strong evidence from in vitro and epidemiologicalstudies that cigarette smoking induces skin damage, triggering clinical signs of skin aging, especially in the perioral and periocular areas. When combined with exposure to solar radiation, the effects are even more pronounced …”
Section: Methodsmentioning
confidence: 99%
“…PM is the sum of all the solid and liquid particles suspended in air, and this complex mixture includes both organic and inorganic particles, such as dust, pollen, soot, smoke and liquid droplets. The toxicity of PM is caused not only by its cell‐permeable size but also by the combination of various substances . Numerous epidemiological investigations into ambient air pollution have indicated that PM is correlated not only with an exacerbation of cardiovascular diseases and with an impact on respiratory system inflammation but also with the progression of inflammatory skin diseases such as atopic dermatitis, acne, psoriasis and allergic reactions .…”
Section: Introductionmentioning
confidence: 99%